Improved antioxidant status after diet supplementation with novel natural-based supplement in combat athletes - Tirla, A.; Vicas, S., I.; Sirca, T., B.; Cinezan, C.; Cavalu, S. (Sports, 2024)
Background: Intense physical activity is known to generate high levels of oxidative stress, and supplementation with bioactive products with powerful antioxidant effects is often recommended. In this context, the present study aims to evaluate the potential benefits of supplementing the diet of professional combat fighters with a new bioactive formulation based on Aronia melanocarpa (black chokeberry) and bee pollen, a natural combination with a balanced ratio of macro- and micronutrients, rich in proteins and polyphenols.